P142 Restriction of use of high cost drugs for the treatment of rheumatoid arthritis by CCGs in England. (26th April 2021) - Walker, David; Robinson, Sandra; Barry, Jane; Punter, Phillip; Kearns, Sinead
Abstract: Background/Aims   It became apparent at a session at the 2019 BSR Annual Conferene that some CCGs were restricting the number of high cost drugs (HCDs) that were permitted to be prescribed for an individual with rheumatoid arthritis. Further HCDs could only then be prescribed by utilising an Individual Funding Request. We were interested to explore how common this was and what the restrictions were in different areas. Methods   The websites of all CCGs in England were scrutinised between March and July 2020 for local guidelines for the use of HCDs in patients with rheumatoid arthritis (RA). The results were tabulated and mapped. Results   Of 134 CCGs in England, 69 (51%) had no expressed restriction on numbers of HCDs provided that NICE thresholds were observed. 10 (7%) had a pathway limiting the drugs to 6, 49 (33%) restricted to 4 and a further 9 (7%) restricted to 3. Dates of guidance implementation varied from 07/2017 to 07/2020 with the vast majority being 2018 and 2019. Geographically, the restrictions were not uniform. The CCGs restricting to 3 HCDs were all in London except for one, Oxford. Those restricting to 4 were mainly from the South East, North West and East. Those restricting to 6 HCDs were in the Liverpool area. Largely unrestricted areas were the North East, the South West, the Midlands and the majority of Yorkshire. The majority of CCGs gave no explanation for the restriction of HCDs. Where stated, the reason given was that it had not been shown to be cost effective. Conclusion   Restricting the number of HCDs may deprive some patients of effective drugs that have been NICE approved contrary to NICE guidance. There are currently 5 different modes of action (MOA) of HCDs (TNFi, B cell depletion, IL6i, CTLA4 and JAKi) for the treatment of moderately or severely active RA, therefore in some areas not even all MOAs may have been tried. There is no reliable way of predicting a patient's response to an individual drug, so it is necessary to trial and observe. Non-responders will require more treatment changes. Many patients have secondary failure of drugs after initial good response, so trying other drugs with the same MOA is a logical progression. Over a long disease course, patients will need many different interventions and access to the widest possible range is important. Whilst there are lower response rates for HCDs in biologic inadequate response phase III studies, responders can be observed after only 3 months of treatment. Restricting the number of drug choices is also likely to affect clinical practice, as less effective drugs could be continued unnecessarily for fear of running out of choices. Disclosure   D. Walker: Honoraria; Gilead Sciences Ltd, Ely Lilly Pharmaceuticals, Pfizer Pharmaceuticals. Grants/research support; Gilead Sciences Ltd. S. Robinson: None. J. Barry: Corporate appointments; Gilead Sciences Ltd. P. Punter: Corporate appointments; Gilead Sciences Ltd. S. Kearns: Corporate appointments; Gilead Sciences Ltd.